Life cycle assessment of a circular, urban mushroom farm. (15th March 2021) - Dorr, Erica; Koegler, Maximilien; Gabrielle, Benoît; Aubry, Christine
Abstract: Modern food systems incur many environmental impacts, which can be mitigated by the application of circular economy principles, such as the closing of material and energy loops and the upcycling of waste products. Mushroom farming provides a relevant case in this direction because organic waste can be used for substrate as an input in the cultivation process, which produces valuable outputs such as edible foodstuffs and soil amendment. Few studies evaluate the actual environmental impacts of circular food production systems and assess their efficacy with respect to more linear alternatives. To address this research gap, we quantified the environmental impacts of a circular, urban mushroom farm next to Paris, France. We used life cycle assessment to study the production of 1 kg of fresh oyster mushrooms ( Pleurotus ostreatus ), from the generation of substrate materials through delivery to the distribution center. Our goals were to quantify the environmental impacts of a novel type of food production system, to find the aspects of production that contribute most to these impacts, and to assess the advantages and disadvantages of circular economy for this case study. In terms of climate change impact, the product system emitted 2.99–3.18 kg CO2-eq./kg mushroom, and on-farm energy use was the top contributor to all impact categories except land use. Surprisingly, 31% of the climate change impacts came from transport throughout the supply chain, despite the local nature of the farm. Circular economy actions helped optimize the environmental performance by minimizing impacts from the use of materials, which were mostly upcycled. This suggests that further improvements could be made by reducing energy consumption on the farm or by making the transport schemes more efficient, rather than continuing to focus on the type and source of materials used. This circular, urban farm had similar climate change impacts to classical, more linear systems, but these impacts could be largely reduced by implementing appropriate actions. These were identified and discussed with the farmers, factoring in their feasibility. Highlights: Climate change impacts were 2.99–3.18 kg CO2 eq. per kilogram of fresh mushroom. A large portion of environmental impacts came from energy use on the farm. Circularity led to low impacts from input materials, but high impacts from transport. Improving sanitary measures to increase yield would greatly reduce impacts. Impacts were similar to typical mushroom farms, but can be much lower if optimized.